2005
DOI: 10.1021/jf048542d
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR Method for Use in Real-Time PCR for Identification of Fish Fillets from Grouper (Epinephelus and Mycteroperca Species) and Common Substitute Species

Abstract: Mitochondrial 16S rRNA sequences from morphological validated grouper (Epinephelus aeneus, E. caninus, E. costae, and E. marginatus; Mycteroperca fusca and M. rubra), Nile perch (Lates niloticus), and wreck fish (Polyprion americanus) were used to develop an analytical system for group diagnosis based on two alternative Polymerase Chain Reaction (PCR) approaches. The first includes conventional multiplex PCR in which electrophoretic migration of different sizes of bands allowed identification of the fish speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…Molecular markers used in the multiplex fingerprinting technique for the authentication, control, and inspection of fishery stocks are based on the design of specific oligonucleotides and markers derived from the sequencebased amplification of the 5S, 12S, 18S (Asensio, 2008, Asensio et al, 2009, 16S (Ulrich et al, 2013), Cyt b (Melo Palmeira et al, 2013), and COI genes , as well as fragment length polymorphisms, RFLPs (Paine et al 2007;Torres et al 2013) or even nuclear markers, such as ITS 2 (Feldheim et al, 2010), SNPs (Torres et al, 2013) and microsatellites (Rodrigues et al, 2011), and realtime PCR techniques (Trotta et al, 2005). The COI gene is a highly effective and reliable tool for the diagnosis of the authenticity of fishery products (Veneza et al, 2014), and the multiplex PCR technique has proven especially effective for the detection of endangered species De-Franco et al, 2010;Alexandre de-Franco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular markers used in the multiplex fingerprinting technique for the authentication, control, and inspection of fishery stocks are based on the design of specific oligonucleotides and markers derived from the sequencebased amplification of the 5S, 12S, 18S (Asensio, 2008, Asensio et al, 2009, 16S (Ulrich et al, 2013), Cyt b (Melo Palmeira et al, 2013), and COI genes , as well as fragment length polymorphisms, RFLPs (Paine et al 2007;Torres et al 2013) or even nuclear markers, such as ITS 2 (Feldheim et al, 2010), SNPs (Torres et al, 2013) and microsatellites (Rodrigues et al, 2011), and realtime PCR techniques (Trotta et al, 2005). The COI gene is a highly effective and reliable tool for the diagnosis of the authenticity of fishery products (Veneza et al, 2014), and the multiplex PCR technique has proven especially effective for the detection of endangered species De-Franco et al, 2010;Alexandre de-Franco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al (2015) has shown the DNA barcoding to be an effective molecular tool for the detection of commercially-valuable species such as the groupers, while Torres et al (2013) successfully applied PCR RFLP and SNP detection techniques to the identification of specimens of E. itajara, E. morio, M. bonaci, and M. marginata. The multiplex PCR technique, based on the COI gene Mendonça et al, 2010) and other mitochondrial (Trotta et al, 2005;Hashimoto et al, 2010;Ravago-Gotanco et al, 2010) and nuclear genes (Shivji et al, 2002;Chapman et al, 2003;Rodrigues et al, 2011), has proven to be an efficient and rapid low-cost tool that is safe and easy to apply (Abercrombie et al, 2005). This technique permits the identification of illegal fishing by the authorities, even when the catches have been processed for consumption, and contribute to conservation practices on a worldwide scale .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for instance, Sotelo et al [26] used the TaqMan assay for the identification and quantification of Cod (Gadus morhua). Trotta et al [30] used the Real-Time PCR for the identification of fish fillets from Grouper (Genera Epinephelus and Mycteroperca) and common substitute species. Hird et al [5] The development of analytical methods for fish species identification may help to detect and avoid willful, as well as unintentional substitution of different fish species and thus enforce labeling regulations [2,12,15,29].…”
Section: Taqman Real-time Pcr Methodsmentioning
confidence: 99%
“…86 Such a tool could also be used for detection of fraudulent species substitutions in fish markets and fish food products, a practice that is generating concern among consumers. 87 A striking example comes from the Red Snapper (Lutjanus campechanus), which is one of the most economically important fisheries in the Gulf of Mexico, and which has been subject to stringent fishing restrictions due to stock depletion. Marko and colleagues 88 used sequences of the mtDNA gene cytochrome b, in an approach very similar to DNA barcoding, to show that as much as 77% of the L. campechanus fillets were mislabelled in USA markets.…”
Section: The Example Of Fish Dna Barcodingmentioning
confidence: 99%